3D Printing of Multifunctional Hydrogels. (25th March 2019) - Chen, Zhe; Zhao, Donghao; Liu, Binhong; Nian, Guodong; Li, Xiaokeng; Yin, Jun; Qu, Shaoxing; Yang, Wei
Abstract: 3D printing technology has been widely explored for the rapid design and fabrication of hydrogels, as required by complicated soft structures and devices. Here, a new 3D printing method is presented based on the rheology modifier of Carbomer for direct ink writing of various functional hydrogels. Carbomer is shown to be highly efficient in providing ideal rheological behaviors for multifunctional hydrogel inks, including double network hydrogels, magnetic hydrogels, temperature‐sensitive hydrogels, and biogels, with a low dosage (at least 0.5% w/v) recorded. Besides the excellent printing performance, mechanical behaviors, and biocompatibility, the 3D printed multifunctional hydrogels enable various soft devices, including loadable webs, soft robots, 4D printed leaves, and hydrogel Petri dishes. Moreover, with its unprecedented capability, the Carbomer‐based 3D printing method opens new avenues for bioprinting manufacturing and integrated hydrogel devices. Abstract : This paper describes a highly efficient rheology modifier—Carbomer (minimum content 0.5% w/v)—enabled approach for printing multifunctional hydrogels, including double network hydrogels, magnetic hydrogels, temperature‐sensitive hydrogels, and biocompatible hydrogels. Besides the excellent printing performance, mechanical behaviors, and biocompatibility, the printed multifunctional hydrogels enable various soft devices, including loadable webs, soft robots, four‐dimensional printed leaves, and hydrogel Petri dishes.